Investigation on the Compliance of Occupational Safety and Health (OSH) Legislations among Contractors and Potential Interventions to Improve Construction Safety Performance - Koh, Philomena Belia; Nor Haslinda Abas,; Rafikullah Deraman, (International Journal of Sustainable Construction Engineering and Technology, 2022)
The Malaysian construction industry contributes more than one-third of fatalities out of all industries and further proves that safety performance in the construction industry lags behind most other industries. One of the causes is due to the lack integration of technological system and people in safety and health (OSH). This study suggests that one of the ways to avoid accidents at construction site is through an effective OSH management planning tool, with proper management of the interaction between technological systems and people. As an initial step towards the development of the tool, this study aims to investigate the contractors’ compliance with OSH legislation in the Malaysian construction industry. It also attains construction stakeholder’s perceptions of the current situation and intervention to improve OSH performance in the construction industry by providing information or creating a system that can provide information according to the acts and regulations. The information was collected through interviewing selected respondents from several organizations and enforcers in construction industry. The results revealed that the majority of construction organizations followed the OSH requirements, though they did not comprehensively follow them. Lack of knowledge about OSH was also acknowledged by the organizations, even though they were aware about the OSH requirements. The findings also revealed that there is no available tool that can provide information about legislation on OSH requirements which can facilitate the construction teams effectively and lead to prevent an accident happens at the construction site.  Therefore, it is essential to improve the safety performances including provide the guidelines of the OSH according to the acts and requirements and enhancing the management in improving the safety at construction sites.